16th Annual North American Waste-to-Energy Conference 2008
DOI: 10.1115/nawtec16-1911
|View full text |Cite
|
Sign up to set email alerts
|

High Electrical Efficiency by Dividing the Combustion Products

Abstract: Energy recovery from waste is an efficient way to reduce emissions of greenhouse gas and other gaseous, liquid and solid pollutants and thereby to contribute to a sustainable development. Waste fired power plants are an important part of the European waste management system, and the demands made to modern waste fired power plant are very focused on high electrical output. Lately, Babcock & Wilcox Vo̸lund (BWV) and the CHEC research centre at the Technical University of Demnark has developed a new technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In cases 4, 5 and 6 the WtE plant is assumed to be a CHP installation and that there is constant annual demand for heat from the (Madsen et al, 2008) were considered. The study found that the increase of steam temperature and pressure could increase the electrical efficiency and more specifically if the temperature increased from 400°C to 500°C and the pressure from 50 bar to 80 bar the electrical efficiency could be increased by 3%.…”
Section: Energy Efficiency Assessment Of the Wte Facilitymentioning
confidence: 99%
“…In cases 4, 5 and 6 the WtE plant is assumed to be a CHP installation and that there is constant annual demand for heat from the (Madsen et al, 2008) were considered. The study found that the increase of steam temperature and pressure could increase the electrical efficiency and more specifically if the temperature increased from 400°C to 500°C and the pressure from 50 bar to 80 bar the electrical efficiency could be increased by 3%.…”
Section: Energy Efficiency Assessment Of the Wte Facilitymentioning
confidence: 99%
“…Because of corrosive deposits forming on the superheater surfaces, the superheater steam temperature in WtE boilers is usually kept below approximately 420 °C to minimize corrosion, which would otherwise require frequent replacement of superheaters . At a superheated steam temperature of approximately 380−420 °C and 50 bar, an electrical efficiency of 20−25% is obtained …”
Section: Introductionmentioning
confidence: 99%
“…In 2005, a few concentration measurements of Cl, Na, K, Ca, S, Pb, and Zn were carried out above the grate at the Vestforbrænding unit 5. ,, Some limitations of the measurement equipment were experienced during those experiments. It was not possible to reuse the probes during the experiments, and therefore, only a limited number of experiments was conducted with no reproduction of the obtained results.…”
Section: Introductionmentioning
confidence: 99%